Changes of lipid oxidation products content in ventricles of the rat heart as a result of electrolyte-steroid cardiomyopathy and correction of this condition - Sverediuk, Yu. A.; Pelykh, V. Ye. (Journal of Education, Health and Sport, 2020)
Cardiovascular disease is one of the leading causes of death in the world. One of such pathologies is metabolic cardiomyopathy. This pathology includes dysfunction of amino acids, lipids, mitochondria, and disease of products accumulation. Conditions that can cause such changes include congenital and acquired hormone levels. A good example is the long-term use of dexamethasone for the treatment of patients with allergies or rheumatology diseases. Electrolyte disturbances are often a concomitant consequence of disease or lifestyle. They also contribute to heart damage under these conditions. Cell damage often begins with damage to cell lipid membranes and is accompanied by accumulation of lipid peroxidation products. The purpose of our study was to investigate diene, triene conjugates and thiobarbituric acid reactive substances levels in the animal ventriculs heart tissue of both sex in conditions of long-term action of dexamethasone and high concentration (4%) solution of sodium chloride in drink water. L-carnitine, as an antioxidant and having the ability to influence to energetic metabolism, apoptosis and transcription of DNA may be a promising means for correction disorders. The experiment was performed with the use of 96 mature white nonlinear rats. Dexamethasone with long-term use promotes the accumulation of diene, triene conjugates and thiobarbituric acid reactive substances (malondialdehyde is main) in the ventricular myocardium of rats of both sexes, more in animals with high content (4%) of NaCl in drinking water, and in males, compared with females. L-carnitine has the ability to significantly offset the negative effects of dexamethasone on the content of lipoperoxidation products in the ventricular myocardium of rats of both sexes, including against the background of increased salt content in drinking water.